LEGAL MECHANISMS IN EUROPEAN UNION AND SERBIA WHICH AIMED TO PROTECT WOMEN FROM DOMESTIC VIOLENCE - Samardžić, Sandra (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Violence against women is the most common form of domestic violence. This problem has long been ignored, because it is considered that family relations, e.g. relations between married and unmarried partners are a private matter and the state's obligation was to refrain from any interference. However, since the problem of domestic violence against women has become increasingly common, the attitude of the international community began to change, and it was increasingly emphasizes the need to create adequate legal mechanisms to provide protection to the victim. In this sense, in the United Nations, and the European Union a number of laws were enacted. In Serbia, there is also both, criminal and civil law  regulation that seeks to prevent domestic violence and to punish perpetrators and protect victims. In addition to adequate legal mechanisms, which can always be improved, it is necessary to take certain initiatives by states that can lead to improved awareness among the people about the presence of violence, and the ways in which they can help.